Tracking the establishment of local endemic populations of an emergent enteric pathogen. - Holt, K; Thieu Nga, T; Thanh, D; Vinh, H; Kim, D; Tra, V; Campbell, J; Hoang, N; Vinh, N; Minh, P; Thuy, C; Nga, T; et al. (2013)
Shigella sonnei is a human-adapted pathogen that is emerging globally as the dominant agent of bacterial dysentery. To investigate local establishment, we sequenced the genomes of 263 Vietnamese S. sonnei isolated over 15 y. Our data show that S. sonnei was introduced into Vietnam in the 1980s and has undergone localized clonal expansion, punctuated by genomic fixation events through periodic selective sweeps. We uncover geographical spread, spatially restricted frontier populations, and convergent evolution through local gene pool sampling. This work provides a unique, high-resolution insight into the microevolution of a pioneering human pathogen during its establishment in a new host population.